Analisis Niat Berwirausaha Pada Mahasiswa Program Profesi Ners - Kaparang, Grace Fresania; Langingi, Nova Lina; Pintunaung, Daniel (Nutrix Journal; Vol 7 No 1 (2023): Volume 7, Issue 1, 2023, 2023)
The high unemployment rate in Indonesia, especially for bachelor and diploma graduates in productive age level is a challenge for educational institutions to educate entrepreneurship students thus as graduates they can create jobs and not job seekers. The study aimed to investigate the entrepreneurial intentions of students in the nursing professional program at Klabat University with descriptive research design and convenience sampling and 102 participants enrolled. Furthermore, researchers adopted a valid questionnaire. The results of this study found that the entrepreneurship intention of students in the nursing professional program at Klabat University was moderate or tended to be high (M=4,45; SD=0,97), indicating that students proportionally chose to be employees and entrepreneurship and even tended to be entrepreneurs. In frequency, the majority of the students are in the category of “moderate” in their entrepreneurial intention (n=60; 58,82%).  It is recommended for educational institutions to provide entrepreneurial training or apprenticeships for students so that the desire for entrepreneurship can be increased and for future researchers to compare the entrepreneurial intentions of two students from different faculties also to explore the factors influencing entrepreneurial intentions in nursing professional students. Abstrak Tingginya angka penggangguran di Indonesia terlebih lulusan sarjana dan diploma yang masuk dalam usia produktif menjadi tantangan bagi institusi pendidikan untuk mendidik mahasiswa berwirausaha sehingga ketika tamat dapat menciptakan lapangan kerja dan bukan pencari kerja. Itulah sebabnya penelitian ini dilakukan untuk mengetahui niat berwirausaha mahasiswa program profesi ners di Universitas Klabat dengan deskriptif sebagai desain penelitian dan convenience sampling . 102 partisipan bersedia untuk ikut serta dalam penelitian. Selanjutnya peneliti mengadopsi kuesioner valid dan reliabel. Hasil penelitian ini didapati bahwa niat berwirausaha mahasiswa program profesi ners Universitas Klabat adalah sedang atau cenderung mengarah ketinggi (M=4,45; SD=0,97), yang artinya adalah mahasiswa secara proporsional memilih sebagai karyawan dan juga berwirausaha dan bahkan cenderung untuk berwirausaha. Dari hasil distribusi frekuensi juga, mayoritas mahasiswa juga berada pada kategori sedang (n=60; 58,82%). Direkomendasikan kepada institusi pendidikan untuk memberikan pelatihan atau magang wirausaha bagi mahasiswa sehingga niat wirausaha dapat ditingkatan dan bagi peneliti selanjutnya untuk membandingkan niat berwirausaha dari dua mahasiswa fakultas yang berbeda serta menggali faktor-faktor mempengaruhi niat berwirausaha pada mahasiswa profesi ners. Kata K unci :  niat berwirausaha, mahasiswa profesi ners